Improvement of wear Resistance Properties of Metal Gears using Laser Surface Hardening (London Journal of Engineering Research, 2024)
This study investigates the efficacy of laser surface hardening (LSH) as a method to enhance the wear resistance of metal gears, comparing it with traditional hardening techniques such as induction and flame hardening. The LSH process involves using a high-energy laser beam to rapidly heat the gear surface, resulting in microstructural changes that increase hardness and wear resistance. Experiments were conducted using two common gear steels, JIS-SCM415 and JIS-S45C, with the laser parameters optimized to achieve the desired hardness profile. The results showed that the best hardening was achieved with a laser power of 1000W, scanning speed of 100mm/s, and a spot size of 1mm, resulting in a surface hardness of 672 HV and a core hardness of 502 HV. Wear testing indicated that the wear rate of laser-hardened gears was comparable to new conventional gears, with a weight loss of 10-12 mg/hr. The study demonstrates that LSH can significantly improve the wear resistance of gears, with minimal distortion and precise control over the hardened depth, making it a promising alternative to conventional hardening methods for enhancing gear longevity and performance
Keywords: bitumen; modification. styrene-butadiene rubber; butyl rubber; rubber waste; polymer-bitumen composition; physical and mechanical properties; dolomite